Fugitivity and marronage and the study of sex work - O'Connell Davidson, Julia (Frontiers in Sociology, 2023)
Campaigns against female prostitution used slavery as a rhetorical device to characterize the condition of sex workers, and sex work features prominently in contemporary campaigns against “modern slavery”. In both types of campaigning, “the slave” is worked as a symbolic device to represent the abject condition of human beings objectified, controlled by violence or its threat, and stripped of agency and choice. The assumptions and generalizations about prostitution that inform this vision have been extensively critiqued. However, less attention has been paid to the fact that the analogy also rests on a very particular reading of “the slave” and a very partial appeal to histories of Atlantic World slavery. Histories of enslaved people's resistance and flight are entirely overlooked. The latter has recently prompted interest in fugitivity and marronage as analytic concepts, albeit concepts that are defined and deployed in different ways by different scholars and activists. This review asks whether and how they might potentially have theoretical purchase with regard to the contemporary experience (both positive and negative) of sex workers.